Sodium Channel Nav1.8 Underlies TTX-Resistant Axonal Action Potential Conduction in Somatosensory C-Fibers of Distal Cutaneous Nerves - Klein, Amanda H.; Vyshnevska, Alina; Hartke, Timothy V.; De Col, Roberto; Mankowski, Joseph L.; Turnquist, Brian; Bosmans, Frank; Reeh, Peter; Schmelz, Martin; Carr, Richard W.; Ringkamp, Matthias (The Journal of Neuroscience, 2017)
Voltage-gated sodium (NaV) channels are responsible for the initiation and conduction of action potentials within primary afferents. The nine NaVchannel isoforms recognized in mammals are often functionally divided into tetrodotoxin (TTX)-sensitive (TTX-s) channels (NaV1.1-NaV1.4, NaV1.6-NaV1.7) that are blocked by nanomolar concentrations and TTX-resistant (TTX-r) channels (NaV1.8 and NaV1.9) inhibited by millimolar concentrations, with NaV1.5 having an intermediate toxin sensitivity. For small-diameter primary afferent neurons, it is unclear to what extent different NaVchannel isoforms are distributed along the peripheral and central branches of their bifurcated axons. To determine the relative contribution of TTX-s and TTX-r channels to action potential conduction in different axonal compartments, we investigated the effects of TTX on C-fiber-mediated compound action potentials (C-CAPs) of proximal and distal peripheral nerve segments and dorsal roots from mice and pigtail monkeys (Macaca nemestrina). In the dorsal roots and proximal peripheral nerves of mice and nonhuman primates, TTX reduced the C-CAP amplitude to 16% of the baseline. In contrast, >30% of the C-CAP was resistant to TTX in distal peripheral branches of monkeys and WT and NaV1.9-/-mice. In nerves from NaV1.8-/-mice, TTX-r C-CAPs could not be detected. These data indicate that NaV1.8 is the primary isoform underlying TTX-r conduction in distal axons of somatosensory C-fibers. Furthermore, there is a differential spatial distribution of NaV1.8 within C-fiber axons, being functionally more prominent in the most distal axons and terminal regions. The enrichment of NaV1.8 in distal axons may provide a useful target in the treatment of pain of peripheral origin.SIGNIFICANCE STATEMENTIt is unclear whether individual sodium channel isoforms exert differential roles in action potential conduction along the axonal membrane of nociceptive, unmyelinated peripheral nerve fibers, but clarifying the role of sodium channel subtypes in different axonal segments may be useful for the development of novel analgesic strategies. Here, we provide evidence from mice and nonhuman primates that a substantial portion of the C-fiber compound action potential in distal peripheral nerves, but not proximal nerves or dorsal roots, is resistant to tetrodotoxin and that, in mice, this effect is mediated solely by voltage-gated sodium channel 1.8 (NaV1.8). The functional prominence of NaV1.8 within the axonal compartment immediately proximal to its termination may affect strategies targeting pain of peripheral origin.
EVALuna2:33345